Rare bird documentation form for Glaucous Gull at Lock and Dam 14, 1980 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1980)
Rare bird documentation form for a Glaucous Gull at Lock and Dam 14 in Scott County, IA on December 21, 1980. Epson - sheet feed